Politics of 'Leaving No One Behind': Contesting the 2030 Sustainable Development Goals Agenda. Issue 3 (16th April 2017) - Weber, Heloise
Abstract: In this article, I develop a critical analysis of the Sustainable Development Goals (SDGs) agenda and its commitment to 'leave no one behind'. The Preamble to the Resolution on the SDGs adopted by the United Nations General Assembly stated the following: 'We are resolved to free the human race from the tyranny of poverty and want and to heal and secure our planet. (…) As we embark on this collective journey, we pledge that no one will be left behind'. Through a close examination of the SDG initiative—and aligned concrete policy proposals—I demonstrate that the project to 'leave no one behind' rests on specific ideological premises: it is designed to promote and consolidate a highly contested neo-liberal variant of capitalist development. The SDGs are framed as a universal project, with quite substantial institutional monitoring mechanisms aimed at ensuring the successful implementation of aligned policies. Indeed, as I demonstrate, the implementation of highly contested neoliberal policies are themselves explicit goals of the SDG agenda. In this respect, the SDGs differ significantly from the Millennium Development Goal initiative. The argument I develop demonstrates that the SDG agenda may be aimed in part at undermining political struggles that aspire for more socially just and ecologically sustainable approaches to development. Overall, I argue that the explicit commitment to 'leave no one behind' is a discourse that is strategically deployed to justify the implementation of a highly problematic political project as the framework of global development. This is a framework that privileges commercial interests over commitments to provide universal entitlements to address fundamental life-sustaining needs. Political struggles over development will continue against the ideology of the SDG project and for transformative shifts for actually sustainable development.